Association between algal productivity and phycosphere composition in an outdoor Chlorella sorokiniana reactor based on multiple longitudinal analyses. Issue 5 (25th May 2020) - Steichen, Seth A.; Gao, Song; Waller, Peter; Brown, Judith K.
Summary: Microalgae as a biofuel source are of great interest. Bacterial phycosphere inhabitants of algal cultures are hypothesized to contribute to productivity. In this study, the bacterial composition of the Chlorella sorokiniana phycosphere was determined over several production cycles in different growing seasons by 16S rRNA gene sequencing and identification. The diversity of the phycosphere increased with time during each individual reactor run, based on Faith's phylogenetic diversity metric versus days post‐inoculation ( R  = 0.66, P  < 0.001). During summer months, Vampirovibrio chlorellavorus, an obligate predatory bacterium, was prevalent. Bacterial sequences assigned to the Rhizobiales, Betaproteobacteriales and Chitinophagales were positively associated with algal biomass productivity. Applications of the general biocide, benzalkonium chloride, to a subset of experiments intended to abate V. chlorellavorus appeared to temporarily suppress phycosphere bacterial growth, however, there was no relationship between those bacterial taxa suppressed by benzalkonium chloride and their association with algal productivity, based on multinomial model correlations. Algal health was approximated using a model‐based metric, or the 'Health Index' that indicated a robust, positive relationship between C. sorokiniana fitness and presence of members belonging to the Burholderiaceae and Allorhizobium–Neorhizobium–Pararhizobium–Rhizobium clade. Bacterial community composition was linked to the efficiency of microalgal biomass production and algal health. Abstract : Microalgae can be efficiently cultivated to produce biomass suitable for conversion to liquid biofuels. Long term experiments conducted over multiple growing seasons in the arid Southwest region of the United States revealed significant associations between algal productivity and the bacterial members of the culture phycospheres. These species offer targets for improving algal biomass yields in mass cultivation.